Óleo essencial de Cymbopogon martinii e seu constituinte majoritário geraniol : influência na mortalidade e comportamento de Apis mellifera (Apidae) - Santos, Ane Caroline Celestino (2017)
The bees Apis mellifera are one of great economic and ecological importance because they are efficient pollinators in natural and agricultural environments. The recent decline of bee colonies around the world has been attributed to several causes, including the use of neonicotinoid insecticides. Despite this, the use of these products has increased in recent decades on a global scale. In an attempt to evaluate an alternative to the use of neonicotinoids, in this work we analyzed the effects of the essential oil of Cymbopogon martinii and its major compound on Apis mellifera bees. For this, the bees were exposed, by contact and ingestion, to C. martinii essential oil, geraniol and commercial insecticide imidacloprid, in order to evaluate the toxicity, behavioral and locomotion effects of bees treated with these compounds. The tests were conducted in the laboratory using individuals from A. mellifera. Our results showed that the highest toxicity occurs through the ingestion route and the imidacloprid causes higher mortality to the bees than the other treatments. Although there was no behavioral change (individual and collective) among individuals of the colonies, there was a significant reduction in the locomotion capacity of bees treated with imidacloprid. On the other hand, the bioinsecticides tested did not cause changes in the locomotion of the bees. Thus, our results corroborate the undesirable effects of imidacloprid already reported in the literature, and, above all, it points out the absence of sublethal effects of the essential oil of C. martinii and geraniol and its possible potential alternative to pest management.